Chk1 inhibitor SCH 900776 enhances the antitumor activity of MLN4924 on pancreatic cancer. Issue 2 (17th January 2018) - Li, Jian-ang; Song, Chao; Rong, Yefei; Kuang, Tiantao; Wang, Dansong; Xu, Xuefeng; Yuan, Jian; Luo, Kuntian; Qin, Bo; Nowsheen, Somaira; Lou, Zhenkun; Lou, Wenhui
ABSTRACT: MLN4924 inhibits the cullin-RING ligases mediated ubiquitin-proteasome system, and has showed antitumor activities in preclinical studies, but its effects and mechanisms on pancreatic cancer (PC) remains elusive. We found that MLN4924 inhibited the proliferation and clonogenicity of PC cells, caused DNA damage, particularly double-strand breaks, and leaded to Chk1 activation and cell-cycle arrest. Chk1 inhibitor SCH 900776 alone exhibited minimal cytotoxicity, and caused no DNA damage on PC cells. But in the combination therapy, SCH 900776 enhanced the cytotoxicity and DNA damage caused by MLN4924, likely by abrogating G2/M arrest and promoting DNA re-replication. In vivo study on a xenograft PC mouse model also showed that SCH 900776 increased the efficacy of MLN4924. We also evaluated the level of NEDD8-activating enzyme (NAE), the direct target of MLN4924, and found that NAE level was elevated in PC tissues compared with normal pancreas, but was irrelevant with prognosis. Our findings provide the preclinical evidence and the rationale of the combination therapy of MLN4924 with SCH 900776 or other Chk1 inhibitors to treat PC.